Gematría y poética en “Le città sottili” de Le città invisibili de Italo Calvino - Barrado Belmar, Mari Carmen (Cuadernos de Filología Italiana, 2010)
This work focuses on the study of the relationship between poetics, aesthetics and subtileness- lightness that it is possible to establish in the description carried out by Italo Calvino in “Le città sottili”. As we will see, each one of the five towns that compose this group is characterized by a peculiar architecture, but in all them the absence of weight is appreciated. In the article, besides, the meaning of the name of each city is searched applying the technique of gematry (=conversion of the letters in numbers).